En Route to Targeted Ribosome Editing to Replenish Skin Anchor Protein LAMB3 in Junctional Epidermolysis Bullosa - Bjoern Wimmer; Andreas Friedrich; Katharina Poeltner; Genevieve Edobor; Claudia Mosshammer; Gazmend Temaj; Adriana Rathner; Thomas Karl; Jan Krauss; Joerg von Hagen; Christopher Gerner; Michael Breitenbach; et al. (Elsevier, 2024)
Severe junctional epidermolysis bullosa is a rare genetic, postpartum lethal skin disease, predominantly caused by nonsense/premature termination codon (PTC) sequence variants in LAMB3 gene. LAMB3 encodes LAMB3, the β subunit of epidermal-dermal skin anchor laminin 332. Most translational reads of a PTC mRNA deliver truncated, nonfunctional proteins, whereas an endogenous PTC readthrough mechanism produces full-length protein at minimal and insufficient levels. Conventional translational readthrough-inducing drugs amplify endogenous PTC readthrough; however, translational readthrough-inducing drugs are either proteotoxic or nonselective. Ribosome editing is a more selective and less toxic strategy. This technique identified ribosomal protein L35/uL29 (ie, RpL35) and RpL35-ligands repurposable drugs artesunate and atazanavir as molecular tools to increase production levels of full-length LAMB3. To evaluate ligand activity in living cells, we monitored artesunate and atazanavir treatment by dual luciferase reporter assays. Production levels of full-length LAMB3 increased up to 200% upon artesunate treatment, up to 150% upon atazanavir treatment, and up to 170% upon combinatorial treatment of RpL35 ligands at reduced drug dosage, with an unrelated PTC reporter being nonresponsive. Proof of bioactivity of RpL35 ligands in selective increase of full-length LAMB3 provides the basis for an alternative, targeted therapeutic route to replenish LAMB3 in severe junctional epidermolysis bullosa.